2018
DOI: 10.1021/acs.macromol.8b00036
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Photochromic Polymer Adhesion

Abstract: This paper explores whether the photochromic reaction of a molecule embedded in a polymer film can affect its surface adhesion properties, as measured by shear strength and delamination in water. The adherence of polystyrene (PS) to glass was chosen as a model system. Two commercially available photochromesa spiropyran derivative 1′,3′-dihydro-1′,3′,3′-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2′-(2H)-indole]) (SP) and a diarylethene derivative 1,2-bis(2,4-dimethyl-5-phenyl-3-thienyl)-3,3,4,4,5,5hexafluoro-1-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…42 Although the central focus of this section is to discuss triggering debonding, we note that UV light may also be used to enhance adhesive strength. 69,70 A report from Bardeen and coworkers revealed that UV light can initiate molecular and polymeric movements, which ultimately improves adhesion by increasing interactions at the adhesive-substrate interface. 69 Adhesive liquication via photoisomerization…”
Section: Scope and Focus Of This Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…42 Although the central focus of this section is to discuss triggering debonding, we note that UV light may also be used to enhance adhesive strength. 69,70 A report from Bardeen and coworkers revealed that UV light can initiate molecular and polymeric movements, which ultimately improves adhesion by increasing interactions at the adhesive-substrate interface. 69 Adhesive liquication via photoisomerization…”
Section: Scope and Focus Of This Perspectivementioning
confidence: 99%
“…69,70 A report from Bardeen and coworkers revealed that UV light can initiate molecular and polymeric movements, which ultimately improves adhesion by increasing interactions at the adhesive-substrate interface. 69 Adhesive liquication via photoisomerization…”
Section: Scope and Focus Of This Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, the adhesion reversibility is limited by the permanent changes in the internal polymeric structure. 96 Therefore, high-molecularweight polymer adhesives often find it difficult to achieve a complete debonding and a full recovery due to their high viscosities, which calls for the development of SSSA.…”
Section: Photoresponsive Supramolecular Adhesivesmentioning
confidence: 99%
“…Bardeen and co‐workers embedded SPs into polystyrene (PS) film, and found that UV light irradiation increased the shear strength between the PS film and glass wafer by a factor of 7, due to the closed ‐to‐ open isomerization of SPs. [ 79 ] However, the adhesive force could not completely switch back, because the isomerization of SPs drove the PS chains motion, which further eliminated void spaces and surface gaps at the polymer‐glass interface. An extended system was realized by Read de Alaniz and co‐workers using DASAs as the photoresponsive molecules.…”
Section: Applications On Photoresponsive Systems Of Sps and Dasasmentioning
confidence: 99%